Enhancing Brand Awareness in TikTok: The Impact of Marketing Communication on Social Media Platforms - Segarwati, Yulia; Rakhmaniar, Almadina; Azka, Zahrah; Gunawan, Iwan; Jamaludin, Maun (Research Horizon, 2023)
Market orientation is crucial for companies in the face of global competition and evolving customer demands, as companies realize the need for continuous adaptation. This research delves into the influence of "Bittersweet by Najla's" marketing communication on the TikTok social media platform on brand awareness. Using a quantitative approach, data was collected through surveys from a sample of 327 individuals among the 4.2 million followers of "Bittersweet by Najla" on TikTok, specifically in the city of Bandung. The results validate four hypotheses, affirming that Product, Price, Place, and Promotion significantly affect Brand Awareness. Promotion is found to exert the most substantial influence on brand awareness, highlighting its pivotal role in enhancing brand recognition. These findings underscore the importance of effective marketing communication on social media platforms and carry implications for businesses seeking to elevate their brand awareness in a competitive digital landscape.